Shariah issue of warrant contract: empirical evidence from warrant mispricing in Malaysia market - Qizam, Ibnu; Ardiansyah, Misnen; Haron, Razali (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga Yogyakarta, 2013)
The objective of this paper is to analyze the “gharar” issue of warrant by presenting the empirical evidence of warrant mispricing in Malaysia's market (moneyness and mispricing) and its determinant. The Black Scholes Option Pricing Model (BSOPM) will be used to detect mispricing in a warrant's contract. In addition panel regression will be performed to analyze the determinant if said warrant is mispriced. The result shows that in majority, mispricing happens in warrant, either by Out the Money, or In the Money. Panel regression analysis finds that Stock price, klibor, and maturity are positive and are significant variables to the mispricing of a warrant. Finally, with the use of a warrant mispricing model, this research concludes that there is gharar issue in warrant contract.